Peran Media Sosial dalam Penentuan Pilihan pada Segmen Pemilih Pemula: The Role of Social Media in Making Choices in the Novice Voter Segment - jumiati jumiati (JOURNAL OF GOVERNMENT SCIENCE, 2021)
This study aims to determine the role of social media for novice voter participation in elections. A descriptive literature study is applied with an analysis of previous journals as well as data collection on the same topic through social media, such as Facebook and Twitter. Study findings show that social media has become the main object of novice voters in getting information about elections. Novice voters who are mostly millennials have been introduced to the sophistication of the internet, and exposed by various data through sundry sources. The main information source for the millennial generation, however, is social media, which serves to express their freedom as well as allowing political participation in the digital era. With the imperative position of social media, it is plausible therefore for the government to use it for political socialization aiming at increasing political participation of the novice voters